Molecular Evolutionary Analysis of Potato Virus Y Infecting Potato Based on the VPg Gene - Mao, Yanzhi; Sun, Xuhong; Shen, Jianguo; Gao, Fangluan; Qiu, Guangwei; Wang, Teng; Nie, Xianzhou; Zhang, Wei; Gao, Yanling; Bai, Yanju (Frontiers in Microbiology, 2019)
Potato virus Y (PVY) is an important plant pathogen infecting solanaceous crops, causing significant losses to global potato and tobacco production. Some aspects of the plant pathology and molecular biology of PVY have been studied intensively, but the evolutionary dynamics of this virus are poorly understood. Here, we performed a comprehensive set of rigorous evolutionary analyses using 177 nucleotide sequences of the viral genome linked protein (VPg) gene, which interacts with the plant eukaryotic translation initiation factor 4E (eIF4E). Our Bayesian analysis reveals that the VPg gene of PVY has been evolving at a rate of 5.60 × 10–4 subs/site/year (95% credibility interval 3.35 × 10–4–8.17 × 10–4), which is equivalent to those of other plant-infecting RNA viruses. We identified different evolutionary constraints on the two clades of PVY, clade N and clade O, whose diverge time were estimated at the year 1861 CE (95% credibility interval 1750–1948 CE). We also found that genetic variations were correlated with geographic regions, suggesting that the evolution of this pathogen is strongly affected by geographical associated factors. Taken together, the results of our study have potential implications for the control strategies of PVY.